Clinical applications of concentrated growth factors combined with bone substitutes for alveolar ridge preservation in maxillary molar area: a randomized controlled trial - Shi-chen Lin; Xin Li; Hang Liu; Fang Wu; Lian Yang; Ya Su; Jun Li; Shao-yu Duan (SpringerOpen, 2021)
Abstract Purpose To evaluate the clinical effects of concentrated growth factors (CGFs) combined with bone substitutes for alveolar ridge preservation (ARP) in the maxillary molar area. Methods Thirty-six patients who underwent extraction of the upper molars were recruited and randomly divided into three groups: 1. Grafted with CGFs combined with deproteinized bovine bone mineral (DBBM) and covered with CGFs membrane (CGFs/DBBM group), 2. Grafted with DBBM alone and covered with collagen membrane (DBBM group), 3. Control group spontaneous healing. The area of the alveolar bone in center (C-), mesial (M-) and distal (D-) section was compared with preoperative in radiography. Bone cores were obtained for histopathology observation and comparison. Results In C-, M- and D-section, the alveolar ridge area in all three groups was significantly reduced at 8 months postoperatively compared to the baseline (P < 0.05). The alveolar ridge area declines in the CGFs/DBBM group (C-12.75 ± 2.22 mm2, M-14.69 ± 2.82 mm2, D-16.95 ± 4.17 mm2) and DBBM group (C-14.08 ± 2.51 mm2, M-15.42 ± 3.47 mm2, D-16.09 ± 3.97 mm2) were non-significant differences. They were significantly less than the decline in the control group (C-45.04 ± 8.38 mm2 M-31.98 ± 8.34 mm2, D-31.85 ± 8.52 mm2) (P < 0.05). The percentage of newly formed bone in the CGFs/DBBM group (41.99 ± 12.99%) was significantly greater than that in DBBM group (30.68 ± 10.95%) (P < 0.05). The percentage of residual materials in the CGFs/DBBM group (16.19 ± 6.63%) was significantly less than that in the DBBM group (28.35 ± 11.70%) (P < 0.05). Conclusion Combined application of CGFs and DBBM effectively reduced the resorption of alveolar ridge and resulted in more newly formed bone than the use of DBBM with collagen membranes.